DEVELOPMENT OF AN ORGANIZATIONAL MODEL THAT BRIDGES THE ORGANIZATION-PRACTICE BARRIER IN OVERUSE INJURY PREVENTION: AN ACTION RESEARCH STUDY IN SWEDISH ATHLETICS. Issue 7 (11th March 2014) - Dahlström, Ö; Jacobsson, J; Timpka, T
Abstract : Background: Sports organisations and sportspersons often suffer from an "autonomy-gap" obstructing implementation of interventions against overuse injuries. This obstruction has been described as the organisation-practice (OP) barrier. Objective: To develop an inter-organisational sports safety promotion model targeted at prevention of overuse injuries by identifying initiatives that lastingly will bridge the OP barrier. Design: Participatory action research with focus group interviews using the quality function deployment (QFD) technique. Setting: Swedish athletics involving the Swedish Athletics Association (SAA), clubs, athletes, coaches, and other stakeholders in the sport. Participants: Representatives of Swedish athletics; officials from different divisions of the SAA, coaches, athletes, medical personal, club representatives and parents to youth athletes (year 1: n=12; year 2: n=35). Qualitative data collected and analyzed: Sports needs (Voice of Sports), organizational requirements, organizational changes. Main qualitative outcomes: Organizational facilitators of sports safety promotion targeted at prevention of overuse injuries. Results: An organic sports safety model resulted from the transformation of identified sports needs and organizational requirements into organisational changes. In this model, a dynamic and constantly active organisation-practice membrane reaches across the OP barrier. This organizational membrane consists of an infrastructure supporting continuous exchange of data and information between different actors in athletics. The central component is an Internet-based safety surveillance system covering Swedish athletics as a whole. A 'Safety Forum' is used for safety discussions between athletes, researchers, and SAA representatives, and a 'Coaches' Corner' allows communication between experienced coaches and younger colleagues. Conclusions: An inter-organizational sports safety model facilitating collaboration between sports organisations and sportspersons was developed in the setting of Swedish athletics. The principal feature in the model is an infrastructure supporting continuous exchange of data and information between different actors. Further research is warranted to prospectively evaluate the effectiveness of the novel model in overuse injury prevention.